Effect of size reduction operation on particle size distribution, carotenoid content, hydration and functional characteristics of dehydrated carrot shreds - Haq, Raees ul; Dar, Muhammad Sikander; Kumar, Pradyuman; Prasad, Kamlesh; Nayik, Gulzar Ahmad (Journal of Postharvest Technology, 2022)
The present study involves use of size reduction operation at different intervals of time on particle size distribution of carrot powder. Grinding is  an energy driven process and involves generation of heat that significantly affects the heat liable components at molecular as well as macro  level. A decrease in carotenoid content of around 1.5 to 7.6 % was observed during the grinding operation of carrot shreds at 30 to 150 seconds.  Particle size distribution presented a bimodal curve with finer fractions increasing at the expense of coarse particle upon increasing the time of  operation. A steady increase in water solubility index and water absorption index from 25.84 to 38.14 % and 10.57 to 12.91 g/g respectively,  was observed as particle size decreased towards
Keywords: Carrot; carotenoids; functional properties; hydration characteristics; particle size distribution